Influence of Vacancy Defect on Surface Feature and Adsorption of Cs on GaN(0001) Surface. (7th July 2014) - Ji, Yanjun; Du, Yujie; Wang, Meishan
Abstract : The effects of Ga and N vacancy defect on the change in surface feature, work function, and characteristic of Cs adsorption on a 2 × 2 GaN(0001) surface have been investigated using density functional theory with a plane-wave ultrasoft pseudopotential method based on first-principles calculations. The covalent bonds gain strength for Ga vacancy defect, whereas they grow weak for N vacancy defect. The lower work function is achieved for Ga and N vacancy defect surfaces than intact surface. The most stable position of Cs adatom on Ga vacancy defect surface is at T1 site, whereas it is at B Ga site on N vacancy defect surface. The E ads of Cs on GaN(0001) vacancy defect surface increases compared with that of intact surface; this illustrates that the adsorption of Cs on intact surface is more stable.